The influence of physical fitness and playing standard on pacing strategies during a team-sport tournament - Johnston, R. D.; Gabbett, T. J.; Jenkins, D. G. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To assess the influence of playing standard and physical fitness on pacing strategies during a junior team-sport tournament. Methods: A between-groups, repeated-measures design was used. Twenty-eight junior team-sport players (age 16.6 ± 0.5 y, body mass 79.9 ± 12.0 kg) from a high-standard and low-standard team participated in a junior rugby league tournament, competing in 5 games over 4 d (4 × 40-min and 1 × 50-min game). Players wore global positioning system (GPS) microtechnology during each game to provide information on match activity profiles. The Yo-Yo Intermittent Recovery Test (level 1) was used to assess physical fitness before the competition. Results: High-standard players had an initially higher pacing strategy than the low-standard players, covering greater distances at high (ES = 1.32) and moderate speed (ES = 1.41) in game 1 and moderate speed (ES = 1.55) in game 2. However, low-standard players increased their playing intensity across the competition (ES = 0.57-2.04). High-standard/high-fitness players maintained a similar playing intensity, whereas high-standard/low-fitness players reduced their playing intensities across the competition. Conclusions: Well-developed physical fitness allows for a higher-intensity pacing strategy that can be maintained throughout a tournament. High-standard/low-fitness players reduce playing intensity, most likely due to increased levels of fatigue as the competition progresses. Low-standard players adopt a pacing strategy that allows them to conserve energy to produce an "end spurt" in the latter games. Maximizing endurance fitness across an entire playing group will maximize playing intensity and minimize performance reductions during the latter stages of a tournament.